The genome sequence of the endemic Mexican common mustached Bat, Pteronotus mexicanus. Miller, 1902 [Mormoopidae; Pteronotus] - Sánchez-de la Vega, Guillermo; Gasca-Pineda, Jaime; Martínez-Cárdenas, Anahí; Vernes, Sonja C.; Teeling, Emma C.; Mai, Meike; Aguirre-Planter, Erika; Eguiarte, Luis E.; Phillips, Caleb D.; Ortega, Jorge (Gene, 2024)
•This manuscript is based on the description of the genome of Pteronotus mexicanus, highlighting its major genomic components.•Our results show a conserved consistency in the different elements of the genomic DNA, consistent with previously reported for other bats . We describe here the first characterization of the genome of the bat Pteronotus mexicanus, an endemic species of Mexico, as part of the Mexican Bat Genome Project which focuses on the characterization and assembly of the genomes of endemic bats in Mexico. The genome was assembled from a liver tissue sample of an adult male from Jalisco, Mexico provided by the Texas Tech University Museum tissue collection. The assembled genome size was 1.9 Gb. The assembly of the genome was fitted in a framework of 110,533 scaffolds and 1,659,535 contigs. The ecological importance of bats such as P. mexicanus, and their diverse ecological roles, underscores the value of having complete genomes in addressing information gaps and facing challenges regarding their function in ecosystems and their conservation.